2022
DOI: 10.3389/fspor.2022.882516
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the Current State and Improvement Opportunities in the Information Flows Necessary to Manage Professional Athletes: A Case Study in Rugby Union

Abstract: In sporting environments, the knowledge necessary to manage athletes is built on information flows associated with player management processes. In current literature, there are limited case studies available to illustrate how such information flows are optimized. Hence, as the first step of an optimization project, this study aimed to evaluate the current state and the improvement opportunities in the player management information flow executed within the High-Performance Unit (HPU) at a professional rugby uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…As organizations strive to enhance their competitive advantage in today's knowledge-based economy, knowledge management has become an increasingly important strategic asset for organizational success ( 4 , 24 26 ). Knowledge transfer is a key component of knowledge management and is concerned with promoting and facilitating knowledge sharing, collaboration, and networking for better decision-making ( 4 , 6 , 26 , 27 ). Our study examined four components of knowledge transfer within the context of academy medical and performance setting.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As organizations strive to enhance their competitive advantage in today's knowledge-based economy, knowledge management has become an increasingly important strategic asset for organizational success ( 4 , 24 26 ). Knowledge transfer is a key component of knowledge management and is concerned with promoting and facilitating knowledge sharing, collaboration, and networking for better decision-making ( 4 , 6 , 26 , 27 ). Our study examined four components of knowledge transfer within the context of academy medical and performance setting.…”
Section: Discussionmentioning
confidence: 99%
“…Since no apparent differences in organizational structures and systems were currently identified between club and federations, further work may be relevant to elucidate the reasons for such differences. Additionally, organizational culture, leadership and technology represent important elements of knowledge strategies for successful knowledge management implementation ( 6 , 28 , 29 ). It is, therefore, likely that several factors beyond the reach of the current study contribute to the reported limitations in knowledge transfer currently observed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Professional rugby clubs are unique due to the attritional nature of the sport. Simply expressed, this means that club owners and club administrators are required to properly manage the interests of their players first [ 37 ]. Previous research into this area has suggested that players view themselves as “commodities” and that injury was viewed as an “occupational hazard” within rugby union [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…3 Research illustrates that such decision-making processes involve the interactions between multiple stakeholders. [4][5][6] In such contexts, under the absence of adequate standards or research-based guidelines, practitioners engaged in a collective decision-making process may create evidence from information sources based primarily on their own personal biases rather than aligning with holistic organisational objectives. 7 This in turn has the potential to create noise in decision-making relating to player management.…”
Section: Introductionmentioning
confidence: 99%